2021
DOI: 10.1016/j.labeco.2021.101981
|View full text |Cite
|
Sign up to set email alerts
|

Does online search improve the match quality of new hires?

Abstract: This paper studies the effects of the high-speed internet expansion on the match quality of new hires. We combine data on internet availability at the local level with German individual register and vacancy data. Results show that internet availability has no major impact on the stability of new matches and their wages. We confirm these findings using vacancy data, by explicitly comparing match outcomes of online and non-online recruits. Further results show that online recruiting not only raises the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Second, other websites are not associated with better‐quality matches or longer vacancy durations than those from non‐Internet channels, even though they do lead to the examination of more applications. With the notable exception of matches via the company's website, these results are in line with those in Gürtzgen et al (2021), who found no major effect of online recruitment on match quality, as measured by the wages of new hires.…”
Section: Estimation Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Second, other websites are not associated with better‐quality matches or longer vacancy durations than those from non‐Internet channels, even though they do lead to the examination of more applications. With the notable exception of matches via the company's website, these results are in line with those in Gürtzgen et al (2021), who found no major effect of online recruitment on match quality, as measured by the wages of new hires.…”
Section: Estimation Resultssupporting
confidence: 90%
“…They will thus have lower average satisfaction than successful recruiters. Nevertheless, Gürtzgen et al (2021) found that online search does not significantly increase the probability of recruitment failure, so that this bias may be minor. Note: The first four outcomes are modeled via probit regressions, and the last two, ordered, outcomes by ordered probit regressions.…”
Section: Do Hiring Outcomes Depend On the Website Used For Recruitment?mentioning
confidence: 95%
See 1 more Smart Citation
“…Several other studies have used distance from the network node as an exogenous source of variation of Internet exposure. Gurtzgen et al (2021) and Gürtzgen et al (2021) combined information on the geolocation of Germany's broadband network nodes with the Integrated Employment Biographies of German workers provided by the Federal Employment Agency to assess the impact of the Internet on workers' employment prospects between 1998 and 2008. The authors instrumented Internet availability, gauged as the share of households with the possibility to access a DSL connection in a municipality, with the distance of the nearest LE from each municipality's center (population-weighted).…”
Section: The Topology Of Initial Broadband Networkmentioning
confidence: 99%
“…Scholars have, in referring to the intrinsic mechanism, tended to use information-seeking theory to explain the off-farm employment-enhancing role that Internet use performs in the case of women. Additionally, they propose that Internet use has led to an increase in the frequency of firm job advertisements by and in job searches by job seekers [17]-they observe that this has improved the efficiency of labor market operations and the quality of career matching. Some scholars also consider the influence of Internet use on rural women's personal behavior.…”
Section: Introductionmentioning
confidence: 99%